Practice of spinal anesthesia among anesthetists in the operation room of referral hospital: Cross-sectional study. (2020) - Ferede, Yonas Admasu; Nigatu, Yonas Addisu; Agegnehu, Abatneh Feleke; Mustofa, Salh Yalew
Abstract: Background: spinal anesthesia is easy to access, cheap safe for surgery done below umbilicus but it has a lot of complications like total spinal, high spinal, hypotension and sever neurological abnormality due to in adequate preparation and poor practice while administration spinal anesthesia in the operation theatres. This audit was aimed to improve practice of spinal anesthesia in our theatre meet the audit standards or not. Methods: This audit was conducted from January 01/2019 to February 01/2019. Anesthetists who administers spinal anesthesia in surgical and obstetric operation rooms were included. Data were collected by direct observation using standardized checklist prepared from recommendations of Ney work Society of Regional Anesthesia (NYSORA). Data were collected prospectively before, during and after administer spinal anesthesia. Results: Total of 50 anesthetists were observed before, during and after they deliver spinal anesthesia. From those audit standards only communication with patients during spinal injection to end of surgery was fully practiced. However, anesthetist should wash their hands, wear sterile gown and the area should be draped with fenestrated drapes in a sterile fashion were not practice. Conclusions: Practice of spinal anesthesia in our operation theatre was satisfactory. But still it needs some improvement that scored below the average and those audit standards that were not practiced at all. Highlights: Administer of Spinal Anaesthesia should always be with assistant. Practice of spinal anaesthesia in our operation theatre was satisfactory. Anaesthetists should sterile before giving spinal anaesthesia. Added vigilance is needed in standards that scored below the average of standards.